Vitamin D-mediated attenuation of miR-155 in human macrophages infected with dengue virus: Implications for the cytokine response - Arboleda, John F.; Fernandez, Geysson J. [UNESP]; Urcuqui-Inchima, Silvio (Elsevier B.V., 2019)
Clinical manifestations of dengue disease rely on complex interactions between dengue virus (DENV) and host factors that drive altered immune responses, including excessive inflammation. We have recently established that vitamin D can modulate DENV-induced cytokine responses and restrict infection in human macrophages. Cytokine responses are finely regulated by several homeostatic mechanisms, including microRNAs (miRNAs) that can rapidly target specific genes involved in the control of immune signaling pathways. However, the modulation of miRNAs by vitamin D during DENV infection is still unknown. Here, using a qPCR miRNA array we profiled immune-related miRNAs induced by DENV infection in human monocyte-derived macrophages (MDM) differentiated in absence or presence of vitamin D (D3-MDM). We found several miRNAs differentially expressed in both MDM and D3-MDM upon DENV infection. Interestingly, from these, a set of 11 miRNAs were attenuated in D3-MDM as compared to MDM. Gene set enrichment analysis of the predicted mRNA targets of these attenuated miRNAs suggested a predominant role of miR-155-5p in the TLR-induced cytokine responses. Indeed, validation of miR-155-5p attenuation in D3-MDM was linked to increased expression of its target gene SOCS-1, a key component for TLR4 signaling regulation. Likewise, TLR4 activation with LPS further corroborated the same miR-155-5p/SOCS-1 negative correlation observed in D3-MDM upon DENV exposure. Moreover, D3-MDM differentiation induced down-regulation of surface TLR4 that was linked to less TLR4/NF-kappa B-derived secretion of IL-1 beta. These data suggest a key role of vitamin D in the control of inflammatory cytokine responses during DENV infection of human macrophages via the TLR4/NF-kappa B/miR-155-5p/SOCS-1 axis.
Keywords: Vitamin D; miRNA-155; TLR4; Immunomodulation; Dengue virus; Cytokine response